Pengaruh Konten Marketing, Online Customer Review dan Desain Produk terhadap Keputusan Pembelian Toko Ummicha Desa Kalen Kecamatan Dlanggu Kabupaten Mojokerto - Muhammad Fiki Dermawan; Nersiwad Nersiwad; Budi Utami (Jurnal bintang manajemen, 2025)
With the existence of online marketing platforms such as TikTok stores that have a significant impact on people’s lives and offer various sales features, digital development is currently expanding. Ummicha Store in Kalen Village, Dalanggu District, Mojokerto Regency, became the location of the study. The purpose of this study was to determine the effect of product design, online customer reviews, and marketing content on purchasing decisions at the Ummicha store. The sample in this study was 140 people, with four variables, namely Product Design (X3), Marketing Content (X1), Online Customer Review (X2), and Purchase Decision (Y1). The population of this study were customers or visitors to the Ummicha store in Kalen Village, Dalanggu District, Mojokerto Regency. The calculated F value of the study was 43.604, which is greater than the F table of 2.671 with a significance level of 5% and a significance level of 0.000. Therefore, it can be concluded that the variables Marketing Content, Online Customer Review, and Product Design on Purchasing Decisions have a significant influence on the purchasing decisions of Ummicha store customers. In the multiple linear regression analysis test of this study, the equation Y = 3.868 + 0.194 X1 + 0.466 X2 + 0.309 X3 was found. After the hypothesis was tested, it was found that purchasing decisions were significantly influenced by all independent variables with a significance value of less than 0.05.